Factors Associated with BPJS Participant Patient Satisfaction with the Quality of Inpatient Services at Malahayati Hospital in 2023 - Cut Roza Asminanda (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
This study aims to analyze factors related to BPJS participant patient satisfaction with the quality of inpatient services at Malahayati Hospital Medan in 2023. The results of the study show that the quality of service provided by Malahayati Hospital Medan is considered good by respondents, with tangibles, quality of service. responsiveness, reliability, assurance, and empathy received good to very good ratings. Research also shows that there has been an increase in services provided by Malahayati Hospital Medan in preparation for hospital accreditation. However, it is recommended that Malahayati Hospital Medan continue to improve service quality, especially in the aspects of reliability and tangibles, while maintaining consistent service quality which is already good in the aspects of responsiveness, assurance and empathy. For further research, it is recommended to conduct more in-depth research regarding service quality, responsiveness, assurance, and empathy using the structural equation model test to identify the smallest variables that influence respondent satisfaction.